U.P dormitory kitchens a study of space utilization and planning - Reyes, Ma. Cristina Ungson
This study is a brief analysis of space utilization and planning in the different dormitory kitchens within the UP Campus. The study provides a satisfactory number of information about the kitchen organization, layout and workflow of the dormitory kitchens, that can be useful in the study of space's functional relationships and distribution. The study tries to find out why such design was used and how such design is serving the needs of its users. Floor plans, work flows and personnel distribution data are shown for a better idea of the nature and flow of activities in the kitchen. With this, we could see the work patterns being employed by the staff in achieving efficient food production and obtaining the goals and objectives of the total organization of the food service. With the food service program's goal of providing the residents and employees with well prepared, palatable, interesting, sanitary and nutritious foods at a low price, the kitchen to be used should be designed in such a way that there is careful consideration given to certain general and specific relationships necessary for its efficient functioning.